SISTEM PENDUKUNG KEPUTUSAN UNTUK PENENTUAN DOSEN PENGAJAR MENGGUNAKAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) DI STISIPOL DHARMA WACANA METRO - Apri Candra Widyawati (Jurnal Informatika, 2014)
STISIPOL DHARMA WACANA evaluate the performance of qualified lecturers and have good skills useful for the determination of the subjects that are taught each semester. Constraints faced is a the lack of system specifically to provide support for the Head of Department at the Department of Public Administration in the decision making. In addition, the supporting data is needed as a basis for decision making comes from part or another agency that the decision making process takes a long time. Based on these constraints, required a method for determining the course lecturer uses a method that is technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The criteria in determining lecturer in the DHARMA STISIPOL Discourse is the assessment of the Department, BAAK, and a questionnaire from students. This research resulted in Decision Support system as recommendations for decision makers determining lecturer membuthkan subjects so that not a long time.Keywords: Decision Support, TOPSIS, Lecturer Course